Audit Penerapan Teknologi Informasi dengan Framework Cobit 4.1 - Mansur, Asmui; Sofalina, Fresa Dwi Juniar (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
PT. Cipta Teknologi Persada is a company engaged in information technology and telecommunications. In its daily operations, this company cannot be separated from the use of information technology to support the company's operations. However, the use of technology in the company has not been evaluated whether it is in accordance with the company's strategy and also whether the company has benefited from the optimal application of information technology or not. For this reason, it is necessary to evaluate the implementation of IT in the company. This research is an analysis of the application of IT at PT. Cipta Teknologi Persada, specifically measuring the level of maturity of IT application using the COBIT 4.1 (Control Objective for Information Technology) framework.